DISTRIBUSI BURUNG KAMPUS ITB JATINANGOR SEBAGAI KAWASAN PENYANGGA HUTAN LINDUNG GUNUNG MANGLAYANG - Permadi, Dikdik; Rasyidi, Rahman; Primadieta, Primadieta (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
In addition educational activities purposes, Jatinangor is used as a buffer zone for several conservation area, such as Protected Forest of Mt. Manglayang. In Perbup Sumedang No. 12 Tahun 2013, Government of Sumedang shows a commitment to maintain environmental quality, particularlyÂ ITB Jatinangor as an eco-oriented campus. Biodiversity inventory is a basic information required for sustainable development programs, as mentioned in UU No.32 Tahun 2009. In this research, biodiversity of birds was selected because of its reliability as parameter in ecological research, ITB Jatinangor was divided into five areas representing general difference of land uses. Method used was point count combined with timed species count. The data was interpreted into Shannon-Wiener index (Hâ), birds distribution in each area, and trophic guild distribution. 42 species from 28 families were recorded with the medium level of diversity (Hâ=2.73). Four Javan endemic species and nine government-protected species were also recorded. Mixed forest had the largest H value, followed by conservation area and the dam, student activity area, monoculture forest, and former rice field. Insectivore species were the most abundant trophic guild (54%) indicating the lack of flowering and fruiting trees. It also showed character of urban environment with high human disturbance.Â Keywords: Â birds, diversity, distribution, ITB Jatinangor